(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
NSAIDs are the drugs that doctors most often prescribe for rheumatoid arthritis. The mechanism of action of NSAIDs is primarily associated with the suppression of the activity of an enzyme called cyclooxygenase. It regulates the synthesis of certain substances that control cellular activity. Due to this, NSAIDs reduce the symptoms of inflammation and pain. As a rule, NSAIDs are used in the treatment of rheumatoid arthritis. They help to cope with chronic pain, inflammation and swelling. But they do not affect the cause of the disease and do not stop the destruction of joints. For most rheumatological diseases, kidney damage portends a poor prognosis and requires aggressive immunosuppressive treatment. On the other hand, it is almost impossible to group NSAIDs by greater or lesser adverse effects on the kidneys - there are very few comparative scientific studies. Thus, it is important to diagnose and treat them at an early stage. But it can be stated that almost all NSAIDs (including selective COX-2 inhibitors) have been described to have adverse effects on the kidneys.